National Healing : Race, State, and the Teaching of Composition - Hurlbert, C. Mark (Utah State University Press, 2012)
"In National Healing, author Claude Hurlbert persuasively relates nationalism to institutional racism and contends that these are both symptoms of a national ill health afflicting American higher education and found even in the field of writing studies. Teachers and scholars, even in progressive fields like composition, are unwittingly at odds with their own most liberatory purposes, he says, and he advocates consciously broadening our understanding of rhetoric and writing instruction to include rhetorical traditions of non-Western cultures. Threading a personal narrative of his own experiences as a student, professor, and citizen through a wide ranging discussion of theory, pedagogy, and philosophy in the writing classroom, Hurlbert weaves a vision that moves beyond simple polemic and simplistic multiculturalism. National Healing offers a compelling new aesthetic, epistemological, and rhetorical configuration."--